Development of information technology for intelligent planning of the IT project team's work based on a flexible methodology - Grinchenko, Marina; Rohovyi, Mykyta; Grinchenko, Evgen (Національний технічний університет "Харківський політехнічний інститут", 2024)
The subject of the study is the development of information technology for intelligent planning of the IT project team. The purpose of the study is to reduce project risks associated with the perception of tasks and their distribution among team members within the project sprint by introducing methods and models for intelligent planning of the IT project team. The information technology is developed on the basis of a set of methods and models, namely: a method for intelligent planning of the IT project team; a model for evaluating a textual description of a task; a method for improving textual descriptions of project tasks; a model for distributing sprint tasks among performers; a method for generating recommendations when planning the work of an IT project team. The use of models related to the processing of textual descriptions of project tasks provides a better understanding of the tasks by the team and increases the efficiency of project implementation. The use of artificial intelligence, including large language models, and stable distribution algorithms in management processes contributes to the automation and efficiency of working with project sprint tasks, increases productivity and team cohesion. The result of the study is an information technology based on the integration of artificial intelligence into sprint planning, task allocation, and risk management. The application of the proposed information technology has significant potential to increase project flexibility, efficiency, and overall success. The developed information technology takes into account the project context and expert opinions, which makes it flexible and adaptive to the specifics of a particular project and team characteristics, which is important for further improving project management processes. The information technology for intelligent planning of the IT project team's work will you to assess and reduce the negative impact of factors that threaten the timing and quality of the project by analyzing historical data and modeling team behavior. Предметом дослідження є розробка інформаційної технологій для інтелектуального планування команди ІТ-проєкту. Мета дослідження – знизити проєктні ризики, які пов’язані зі сприйняттям завдань та їх розподілом між членами команди в рамках проєктного спринту, шляхом впровадження методів і моделей інтелектуального планування команди ІТ-проєкту. Інформаційна технологія розроблена на основі набору методів і моделей, а саме: метод інтелектуального планування команди ІТ-проєкту; модель оцінювання текстового опису завдання; метод удосконалення текстових описів проєктних завдань; модель розподілу завдань спринту між виконавцями; метод генерації рекомендацій при плануванні роботи команди ІТ-проєкту. Використання моделей, які пов’язані з обробкою текстових описів завдань проєкту, забезпечує краще розуміння завдань командою та підвищує ефективність виконання проєкту. Використання штучного інтелекту, що включає великі мовні моделі, і стабільні алгоритми розподілу в процесах управління, сприяє автоматизації та ефективності роботи з проєктними завданнями спринту, що підвищує продуктивність і згуртованість команди. Результатом дослідження стала інформаційна технологія, яка заснована на інтеграції штучного інтелекту при плануванні спринту, розподіл завдань і управління ризиками. Застосування запропонованої інформаційної технології має значний потенціал для підвищення гнучкості, ефективності та загального успіху проєкту. Розроблена інформаційна технологія враховує контекст проєкту та думки експертів, що робить її гнучкою та адаптивною до специфіки конкретного проєкту та характеристик команди, що важливо для подальшого вдосконалення процесів управління проєктами. Інформаційна технологія для інтелектуального планування роботи команди ІТ-проєкту дозволить оцінити та зменшити негативний вплив факторів, що загрожують термінам і якості проєкту, шляхом аналізу історичних даних і моделювання поведінки команди.
Розробка інформаційних технологій для інтелектуального планування роботи команди ІТ-проєкту на основі гнучкої методології
Keywords: intelligent planning; information technology; large language model; method; model; IT team; project management; stable; інтелектуальне планування; інформаційні технології; велика мовна модель; метод; модель; ІТ-команда; управління проєктами; стабільний